ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN TERBAIK PADA PT. WAHYU PERDANA PERSADA DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Ricki, Ricki; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2019)
PT. Wahyu Perdana Persada is one of company which has been located in Jambi where selecting best employment still be selected subjective by owner desire. So always get problem like social jealousy between employment and decrease performance of employment. Because of that, this research have purpose to give solution to that happening problems with offer a prototype of decision support system of selecting best employees with using PHP programming language and MySQL database where writer make development prototype system and using model approach system unified modeling language with use case diagram, activity diagram, class diagram and flowchart diagram. New system make some output like show employees data, admin data, assessment criteria data, employees assessment data, and result of reckoning select best employees with simple additive weighting method (SAW).